Perancangan Sistem Informasi Pengelolaan Limbah Plastik Di CV. Setia Cepti - Efendi, Rustam; hendra, yul; Tarigan, Rehulina (Teknik Informatika Fakultas Ilmu Komputer, 2024)
CV Setia Cepti is engaged in processing plastic waste from raw materials into semi-finished materials. Plastic collected from collectors is crushed into small pieces and stored according to the type of plastic waste. So far, recording transactions for purchasing raw materials from collectors and selling semi-finished materials is still done manually, namely by recording them in books. This creates new problems, namely that sometimes recapitulating all these transactions requires relatively long work and is prone to errors. Apart from that, stock updating errors often occur between the recording and the physical, this happens because officers often miss updating stock because it is still done manually. In developing this system, the author uses the Waterfall method, where system development must be carried out in stages.